Russia's political discourse on the EU's energy transition (2014–2019) and its effect on EU-Russia energy relations. (July 2021) - Romanova, Tatiana
Abstract: Four interpretations of the EU's energy transition can be identified in Russia's political discourse in 2014–2019 based on the matrix that combines realist and liberal approaches to energy relations and the denial or recognition of climate change. The cross-cutting idea of these interpretations is that Russia follows the market logics, whereas the EU either politicises energy relations or chooses economically unreasonable options. Most Russian actors advance all four interpretations in parallel. A liberal interpretation, which recognises climate change, became dominant towards the end of the examined period. Two main policy options are shaped by Russia's political discourse on the EU's energy transition: maintaining the status quo in EU-Russian gas trade and diversifying Russia's export markets. Russia's political discourse reveals a strong ideational difference with the EU on future energy policies, and Russia poorly engages with the EU's post-2030 planning. It is recommended that the EU improve its energy transition communication with Russia, and Russia is advised to enlarge the range of its policy options by better engaging with the EU's long-term energy planning. Russia and the EU also must examine energy transition in the broader context of their relations. Practical project-based cooperation can contribute to ideational convergence between the EU and Russia on future energy policies. Highlights: Four interpretations of the EU's energy transition can be identified in Russia's political discourse. Two policy options are promoted: maintaining gas export and diversification of export markets. Russia's discourse fails to produce policy choices in response to the EU's longer-term planning. The EU could make its energy transition communication in Russia more engaging. The EU and Russia should examine energy transition in the broader context of their relations.